2012
DOI: 10.1007/s00421-012-2342-8
|View full text |Cite
|
Sign up to set email alerts
|

Very short bouts of non-exercise physical activity associated with metabolic syndrome under free-living conditions in Japanese female adults

Abstract: To assess the association between very short daily non-exercise physical activity (PA) lasting <5 min and metabolic syndrome (MS). A total of 42 females (50 ± 6 years) wore a pedometer with a one-axial accelerometer (Lifecorder, Kenz, Japan) to determine the time and the frequency of PA and the moderate to vigorous intensity PA (MVPA). In addition to the PA and the MVPA (PA(all) and MVPA(all)), the PA and MVPA were analyzed based on the bout duration, such as >32 s, >1 min, >3 min, and >5 min (PA(32S), PA(1M),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Most studies investigating bout-accumulated MVPA defined a bout as ≥10 mins of continuous activity above the cut-point threshold [15-17]. Ayabe et al [18] investigated bout durations of <32-s, >1 min, >3 mins and >5 mins in relation with health outcomes. However, there is limited evidence on the influence of allowing shorter or longer bout lengths, and the interaction with cut-point and epoch lengths, on time spent in MVPA in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating bout-accumulated MVPA defined a bout as ≥10 mins of continuous activity above the cut-point threshold [15-17]. Ayabe et al [18] investigated bout durations of <32-s, >1 min, >3 mins and >5 mins in relation with health outcomes. However, there is limited evidence on the influence of allowing shorter or longer bout lengths, and the interaction with cut-point and epoch lengths, on time spent in MVPA in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Both analyses indicate that increasing alcohol intake increases the risk of clustering of MetRFs in non-obese Japanese males. However, earlier studies of MetS have shown a J-shaped relationship between alcohol intake and the risk of MetS [31][32][33]. Indeed, light alcohol consumption was actually associated with a lower risk of MetS [32][33][34], while very heavy alcohol consumption was associated with a substantial increase in the risk of MetS [35].…”
Section: Discussionmentioning
confidence: 76%
“…These results appear to be contradictory. Indeed, both lower physical activity and excess energy intake were reported to be associated with the MetS [8][9][10][11][28][29][30][31]. MetS is, as described above, essentially obesity in combination with a clustering of other MetRFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of MetS have revealed a J-shaped relationship between alcohol intake and the risk of MetS [5][6][7]. Indeed, light alcohol consumption was actually associated with a lower risk of MetS [6][7][8] whereas very heavy alcohol consumption was associated with a substantial increase in the risk of MetS [9].…”
mentioning
confidence: 99%